Features of structure identification the macromodels for nonstationary fields of air pollutions from vehicles - Ocheretnyuk, N.; Voytyuk, I.; Dyvak, M.; Martsenyuk, Ye. (Видавництво Львівської політехніки, 2012)
The main problems of application the genetic algorithms for structure identification of interval difference operator associated with setting its parameters are shown.
Keywords: Method of structure identification; difference operator; genetic algorithm